Design and Simulation of An Electronic Walking Stick For The Blind. - Naherya, Daphine (Kabale University, 2024)
Physical movement is a challenge for visually impaired persons. The walking stick which was used by them is very limited in its range of detection and it is only used to detect the object which is near to the user. The disadvantage of this walking stick is that it fails to detect obstacles outside of its reach. The visually challenged people can avoid the object better if the walking stick can produce vibrations and sound warnings when there is an object in a specific range of distance. The purpose of this study was to design and simulation of an electronic walking stick for the blind.